Structure-based drug design - Brown, Nathan (Henry Stewart Talks, 2016)
Bioisosteres and scaffold hopping, Analogue-by-catalogue, Virtual library design, Homology modelling, Pharmacophore elucidation and searching, Virtual ligand docking